Prevalence of drug-induced metabolic syndrome in patients with severe mental illness at a tertiary care center: a prospective observational study - Shubham Naik; Ian A. Pereira; Jano Zore; Frederick Vaz (MGM Journal of Medical Sciences)
Background: Psychiatric disorders are widespread globally, with evidence suggesting that mortality in most individuals with mental illness is primarily due to somatic diseases. Recent studies have consistently indicated a rising incidence of metabolic syndrome among psychiatric patients, posing a growing concern for both psychiatrists and physicians. Accurately determining the prevalence of metabolic syndrome in individuals with mental illness remains challenging, as results vary due to differences in diagnostic criteria, racial and ethnic backgrounds, and the specific psychiatric disorders prevalent in different regions. Objectives: To assess metabolic disturbances in patients with severe mental illness. Materials and Methods: A prospective observational study was conducted at a tertiary care center in Goa from January 2021 to June 2022, including 300 patients. Results: The overall prevalence of metabolic syndrome was 18.66%. Elevated triglycerides (TGs) were the most frequently observed metabolic abnormality, while increased waist circumference (WC) was the most common factor associated with metabolic syndrome. Statistically significant changes were noted when comparing WC, systolic blood pressure, diastolic blood pressure, fasting blood sugar levels, TGs, and high-density lipoprotein from baseline to follow-ups at two, four, and six months. Although weight and body mass index did not show significant changes at the first follow-up, a statistically significant increase was observed at the second and third follow-ups. Conclusion: While our study’s overall prevalence of metabolic syndrome was relatively low, individual metabolic abnormalities significantly increased over the six-month follow-up period. This trend highlights the heightened risk of cardiovascular and other somatic disorders among psychiatric patients.